Konsep Ithaqah Ibadah Puasa Ramadhan dalam Perspektif Hukum Islam (Studi Kasus Desa Tanjung Bale Kecamatan Sosa) - Syafaruddin; Ahmad Alwi Hutauruk; Mahmudin Hasibuan (Indo Publishing, 2026)
The purpose of this study was to determine: (1) the concept of ithaqah for those observing the Ramadan fast according to Islamic law, and (2) the views of the Tanjung Bale village community, Sosa District, Padang Lawas Regency, regarding the ithaqah for the Ramadan fast. This study is field research, namely research conducted with the aim of intensively studying the background and environment that occurs in a social unit, using a descriptive research approach. The conclusion is that the concept of ithaqah for the Ramadan fast according to Islamic law is the ability to fast without harming the body and internal organs. This means being able to restrain oneself from hunger and thirst, and the genitals from lust. Ithaqah for fasting is a Muslim who is sane, mature, healthy, and settled. The opposite of ithaqah is excuse. Therefore, excuses for fasting in Ramadan include illness, pregnancy, breastfeeding, travel, old age, extreme hunger and thirst, and coercion. Therefore, whenever a sick person misses a fast, they should make up for the missed fast when they have recovered and are healthy. The view of the people of Tanjung Bale village, Sosa District, Padang Lawas Regency regarding the Ithaqah of Ramadhan fasting is to restrain the stomach from food and drink and the genitals from sexual urges or the desire to perform sexual intercourse. Likewise, restraining hearing, sight, speech, hands, feet and all body parts from various sins. Meanwhile, people who have the excuse to fast must have good manners. Because fasting will train oneself and one's desires from evil things within oneself. Because fasting will train oneself and one's desires from evil things within oneself.